Rationale for the technologies of agricultural crops in conditions of uncertainty and risk - Бурлака, Олена Павлівна (Technology audit and production reserves, 2013)
The article describes a way of solution of a problem of obtaining a positive expected outcome in real production conditions, which consists in the choice of technology and machinery complex for their implementation using the methods of economic decision-making in conditions of uncertainty and risk. The initial data for economic decision-making to determine the best alternative technology based on probabilistic nature of the planned crop yields are process maps, compiled and calculated by different methods. The article presents the research, where the author used as input data the results of the calculation of process maps for growing and harvesting sugar beets, obtained by application software, worked out by V. N. Dzyuba, Associate Professor of machinery application and industrial training in Poltava State Agrarian Academy. As a result of analytical studies the author proved that the calculation according to all given criteria justifies the production using the alternative technology A3. Notably, to introduce it to the production the author recommended new intensive technology with the justification of quantitative and qualitative complex of machinery with the objective function to minimize the costs of production. Based on the research the author has concluded that more accurate evaluation of efficiency of the proposed production technologies provides the use of methods of justification of economic decisions in conditions of uncertainty and risk on the basis of criteria of Bayes, Laplace, Hurwitz, Wald, Savage, «maximax» rules, adapted to agricultural production.